2012
DOI: 10.1002/cncr.26675
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated methotrexate, vinblastine, doxorubicin, and cisplatin (AMVAC) as neoadjuvant chemotherapy for patients with muscle‐invasive transitional cell carcinoma of the bladder

Abstract: BACKGROUND:Meta-analysis data demonstrate a 5% absolute survival benefit for neoadjuvant chemotherapy (NAC) using cisplatinbased combination regimens in the radical treatment of muscle-invasive bladder cancer (MIBC). However, there are no randomized, controlled trial data on the optimum regimen. Accelerated methotrexate, vinblastine, doxorubicin, and cisplatin (AMVAC) is a doseintense regimen that has the potential to minimize delays to definitive, potentially curative therapy. A retrospective analysis is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…This is considerably higher than the toxicity incidence of 10-12 % reported in the two prospective neoadjuvant dd-MVAC studies [12,13]. However, our results are in line with dd-MVAC tolerability observed by Blick et al [14]. They reported high-grade toxicities in 26 % of 34 retrospectively analyzed patients who had received 3-4 cycles of dd-MVAC followed by surgery or radiotherapy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This is considerably higher than the toxicity incidence of 10-12 % reported in the two prospective neoadjuvant dd-MVAC studies [12,13]. However, our results are in line with dd-MVAC tolerability observed by Blick et al [14]. They reported high-grade toxicities in 26 % of 34 retrospectively analyzed patients who had received 3-4 cycles of dd-MVAC followed by surgery or radiotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…Currently, available data on efficacy and tolerability of dd-MVAC are largely based on reports in the palliative setting [8,[12][13][14]. The present study was conducted in order to investigate the efficacy and safety of neoadjuvant dd-MVAC, resulting in evident pathological downstaging in patients with locally advanced and/or node-positive urothelial MIBC.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, the dose-dense approach can decrease the time between the start of MVAC chemotherapy and the point of surgery, with a median time of 9.7 weeks reported in the study by Plimack et al 78 (compared with 16–19 weeks for the standard regimens 14,72 ). The results of these two prospective trials 77,78 (TABLE 4), as well as those from two retrospective studies 79,80 , are promising; however, the authors of an editorial 81 , which accompanied the trial publications, identified issues regarding patient selection that might limit the generalizability of the results. For example, both trials included patients with N1 disease, therapy for whom, as previously discussed, cannot truly be considered ‘neoadjuvant’.…”
Section: Improving On Standard Nact With Mvacmentioning
confidence: 99%
“…30,31 A retrospective analysis of 80 consecutive patients who received dose-dense MVAC also generated consistent results. 32 Indeed, several of the centers involved in those studies contributed patient data to RISC, accounting for the predominance of dose-dense MVAC in our MVAC cohort. Although the majority of patients (77%) received dose-dense MVAC in our analysis, no significant difference in the pCR rate was observed between neoadjuvant GC and MVAC.…”
Section: Survivalmentioning
confidence: 99%